MARAHIL, LA MANAHIJ: Categorization of Hadith Critics and the Development of Isnad Criticism (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
The development of ḥadith criticism throughout history demonstrates a complex dynamic, both in terms of the quality and quantity of evaluations, the perspectives of critics, and the types of works produced. Within the tradition of ḥadīth studies, critics are commonly classified into three main categories, mutasyaddid(strict), muʿtadil (moderate), and mutasahil (lenient), based on their evaluative tendencies toward transmitters of ḥadith. However, this categorization has often been accepted taken for granted by subsequent scholars without critical reassessment. As a result, it not only limits the inclusion of new figures within these categories but also perpetuates certain classificatory inaccuracies that have never been reexamined. In response to this problem, the study employs a qualitative approach, utilizing critical historical methods and library research to address two main objectives. First, it reexamines the tripartite classification of ḥadith critics by revisiting the figures most frequently cited within these categories. This analysis reveals the existence of a pattern of periodization that significantly shaped tendencies in ḥadith criticism. Second, the study explores this periodization and its relationship to the emergence and dominance of the zahir al-isnad orientation. The findings demonstrate that the categories of mutasyaddid, muʿtadil, and mutasahil essentially represent stages in the historical periodization of ḥadith criticism (marahil zamaniyyah), rather than methodological approaches (manahij). Consequently, these terms should not be understood as manahij al-jarḥ wa al-taʿdil. While useful as heuristic tools for classification, such categorization oversimplifies the complexity of ḥadith criticism and risks polarizing the field within the narrow framework of the zahir al-isnad school.[Perkembangan kritik hadis sepanjang sejarah menunjukkan dinamika yang kompleks, baik dari segi kualitas dan kuantitas penilaian, perspektif kritikus, maupun jenis karya yang dihasilkan. Dalam tradisi studi hadis, para kritikus sering diklasifikasikan ke dalam tiga kategori utama, yakni mutasyaddid (ketat), mu‘tadil (moderat), dan mutasahil (longgar), berdasarkan kecenderungan penilaian mereka terhadap periwayat hadis. Namun, kategorisasi ini cenderung diterima secara taken for granted oleh para peneliti berikutnya tanpa kajian ulang yang kritis, sehingga tidak hanya menutup kemungkinan masuknya tokoh-tokoh baru dalam kategori tersebut, tetapi juga mempertahankan sejumlah kekeliruan klasifikasi yang tidak pernah direevaluasi. Berangkat dari problem tersebut, penelitian ini menggunakan pendekatan kualitatif dengan metode sejarah kritis dan kajian kepustakaan untuk membahas dua fokus utama. Pertama, mengkaji ulang pengelompokan kritikus hadis ke dalam tiga kategori tersebut dengan melibatkan tokoh-tokoh yang selama ini dijadikan rujukan. Kajian ini mengungkap adanya pola periodisasi yang memengaruhi kecenderungan kritik hadis. Kedua, penelitian ini menganalisis periodisasi tersebut serta kaitannya dengan kemunculan dan dominasi kelompok zhāhir al-isnād. Hasil penelitian menunjukkan bahwa kategori mutasyaddid, mu‘tadil, dan mutasahil sejatinya merepresentasikan tahapan periodisasi kritik hadis (marāḥil zamāniyyah), bukan metode kritik (manāhij). Oleh karena itu, ketiga istilah tersebut tidak tepat dipahami sebagai manāhij al-jarḥ wa al-ta‘dīl. Meskipun berguna sebagai alat bantu klasifikasi, kategorisasi ini terbukti menyederhanakan kompleksitas kritik hadis dan berpotensi mempolarisasi kajian hadis ke dalam kerangka sempit mazhab zhāhir al-isnād.]